Distribution analysis of farmer entrepreneur (MADA) in Kedah and Perlis / Muhammad Adhwa Syahmi Md Taib - Md Taib, Muhammad Adhwa Syahmi (2020)
Muda Agricultural Development Authority (MADA) is the organization that manage and store the data files that involve with the name of the farmer that register under MADA, address of the agricultural activity that been undertaken by the farmer, and others. MADA requires database that integrate with spatial data as well. But, MADA lack of spatial data in terms of locating the farmer activities that register under MADA in Kedah and Perlis. This research was conducted at Perlis and Kedah within the region of MADA. This project aim is to show the distribution of farmers activities in Kedah and Perlis by utilizing of GIS. To achieve the aim, several objectives included which is to plot the activities of farmer entrepreneur of Agro-based and identify the distribution of farmer activities in Kedah and Perlis. Database of Agro Based Entrepreneur Activities and Agro Based Industry Entrepreneur is collected. This study method was used the Hotspot Analysis were made to determine the density of farmer activities either high or low activities in particular area of Kedah and Perlis. Buffer Analysis also been utilized by buffering the main town of Kedah and Perlis within 8 km of radius. Total activities that fall inside of the buffer of main town has been count in order to know which town has the highest or lowest farmer activities. Geographic Information System application was used to utilizing the hotspot map. In conclusion, this study will contribute to the improvement data management for MADA in term of locating the farmer activities using maps.